Requirements on the competence of ICT managers and their coverage by the educational system – experience in the Czech Republic - Doucek, Petr; Maryska, Milos; Novotny, Ota (Journal of Business Economics and Management, 2014)
Global developments in the information society are placing ever greater emphasis on professionals in the area of Information and Communications Technologies (ICT) and especially on managers of ICT companies. This article provides a comparison of the trends in the requirements of business practice on ICT managers in 2006 and 2010 and simultaneously draws attention to the coverage of these requirements by fields of study with ICT specialization, on the example of the Czech Republic. The presented results of the obtained data indicate quite good coverage of the requirements on knowledge and skills for the role of ICT manager in the Czech education market. In addition, the article encompasses methodology that can be employed to compare qualitative quantities of the potential of the educational process with the requirements imposed on it.First published online: 12 Sep 2012